Efek Hepatoprotektif Ekstrak Daun Sirsak (Annona muricata L.) Terhadap Kerusakan Histologis Sel Hepar Mencit (Mus musculus) yang Diinduksi Parasetamol - Riris Arizka Wahyu Kumala; . Suyatmi; Ratih Puspita Febrinasari (Nexus Biomedika, 2014)
Background: Soursop leaves (Annona muricata L.) contains alkaloid, flavonoid, saponin, triterpenoid, and steroid that are potent antioxidant to protect the liver from free radicals. The aim of this research was to know the hepatoprotective effect of soursop leaves extract toward liver histological damage of mice (Mus musculus) induced by paracetamol. Methods: This was an experimental laboratory research with the post test only controlled group design. Samples were 30 male Swiss Webster mice with 2-3 months old and 20g of weight taken by incidental sampling. They were divided randomly into 5 groups, namely kelompok kontrol negatif (KKn), kelompok kontrol (KK), kelompok perlakuan 1 (KP1), kelompok perlakuan 2 (KP2), and kelompok perlakuan 3 (KP3). KKn and KK were given aquadest for 14 days. Soursop leaves extract were given to KP1, KP2, KP3 in dose 5.6 mg, 11.2 mg, and 22.4 mg/20gbw of mice respectively for 14 days. Paracetamol in dose 5.07 g/20gbw were given to KK, KP1, KP2, and KP3 on the 12th, 13th, 14th day. On the 15th day, mice were sacrificed and their livers were taken for histological preparation with paraffin block method and HE staining. Liver histological features were assessed based on quantifying of pyknosis, karhyorhexis, and karyolysis of each 100 cells on the 3rd zone. Data were analyzed using the One-Way ANOVA test (? = 0,05) and continued with Post Hoc (LSD) test (? = 0,05). Results: The results of One-Way ANOVA test showed a significant difference of liver damage score among groups, *p = 0.000. Results of LSD test showed significant difference between KKn-KK, KKn-KP1, KKn-KP2, KKn-KP3, KK-KP1, KK-KP2, KK-KP3, KP1-KP2, KP1-KP3, KP2-KP3 with *p = 0.000 (p < 0.05). Conclusion: Soursop leaves extract (Annona muricata L.) can prevent liver histological damage of mice (Mus musculus) induced by paracetamol.Keywords: Soursop leaves extract, paracetamol, histological damage of liver cell